Utilização de medicamento homeopático em infecções parasitárias : modelo Trypanosoma cruzi - Aleixo, Denise Lessa (2012)
he benznidazole is the only drug available for the etiological treatment of Chagas disease in Brazil. The efficacy of this medication in the chronic phase of the disease is limited, and important adverse effects can compromise the patient's compliance to the treatment. The finding of new compounds that either act on the infection or optimize the action of existing medications can offer benefits to patients. Homeopathy has been extensively used worldwide and, in this sense, it may be an alternative treatment since the action of benznidazole is limited and/or its adverse effects interfere in the continuity of the Treatment. This study consists of three articles in which we show the results of experiments with homeopathic medications in the treatment of Chagas disease. In the first article we develop a bibliographic review with a critical discussion about some aspects of homeopathy in infectious and parasitic diseases. The main aspects related to the effects, the treatment scheme and/or the dynamization used in the experiments are discussed in various articles. The biotherapics are the most widely used highly diluted medication against parasitoses. The issue tackled in the second article was a trial with the biotherapic T. cruzi 17DH in different treatment schemes in Swiss mice infected with the parasite. The results show that the constant administration of the medication brought better benefits, with a reduction of parasitaemia and the prepatent period as well as longer survival periods. In the third article we test the effect of benznidazole highly diluted in different treatment schemes, associated or not with benznidazole in a ponderal dose, in Swiss mice infected with the parasite. Results show a reduction of the adverse effects of benznidazole in a ponderal dose, as well as a clinical improvement of the animals treated with the associations of the medication in a ponderal dose and highly diluted. Therefore, three papers altogether show that the use of homeopathic medicines in parasitic infections in general and, particularly, in the infection with T. cruzi should be further explored.